Incentivize negative emissions responsibly - Bellamy, R (Springer Nature, 2018)
Nation states need to incentivize negative emissions technologies if they are to take the decarbonization of whole energy systems seriously. This incentivization must account for public values and interests in relation to which technologies to incentivize, how they should be incentivized and how they should be governed once incentivized.